Costs of HIV/AIDS treatment in Indonesia by time of treatment and stage of disease. Issue 1 (June 2015) - Siregar, Adiatma; Tromp, Noor; Komarudin, Dindin; Wisaksana, Rudi; van Crevel, Reinout; van der Ven, Andre; Baltussen, Rob
Abstract Background We report an economic analysis of Human Immunodeficiency Virus (HIV) care and treatment in Indonesia to assess the options and limitations of costs reduction, improving access, and scaling up services. Methods We calculated the cost of providing HIV care and treatment in a main referral hospital in West Java, Indonesia from 2008 to 2010, differentiated by initiation of treatment at different CD4 cell count levels (0–50, 50–100, 100–150, 150–200, and >200 cells/mm3 ); time of treatment; HIV care and opportunistic infections cost components; and the costs of patients for seeking and undergoing care. Discussion Before antiretroviral treatment (ART) initiation, costs were dominated by laboratory tests (>65 %), and after initiation, by antiretroviral drugs (≥60 %). Average treatment costs per patient decreased with time on treatment (e.g. from US$580 per patient in the first 6 month to US$473 per patient in months 19–24 for those with CD4 cell counts under 50 cells/mm3 ). Higher CD4 cell counts at initiation resulted in lower laboratory and opportunistic infection treatment costs. Transportation cost dominated the costs of patients for seeking and undergoing care (>40 %). Conclusions Costs of providing ART are highest during the early phase of treatment. Costs reductions can potentially be realized by early treatment initiation and applying alternative laboratory tests with caution. Scaling up ART at the community level in certain high prevalence settings may improve early uptake, adherence, and reduce transportation costs.